‘Sin is Rightly Called the Punishment of Sin’: Francis Turretin’s Reformed Doctrine of Sin - Cumming, Nicholas A. (Reformation & Renaissance review, 2020)
This article contextualizes Francis Turretin’s (1623-87) doctrine of sin, and in particular his understanding of sin as a punishment for sin. Specifically, it elaborates on the theological context into which Turretin speaks. Through analyzing Turretin’s historical situation, it progresses to the content of Turretin’s theology in light of his theological and political opponents. Utilizing Turretin’s Institutes of Elenctic Theology (1679-1685), St Augustine’s Contra Julianum, and John Calvin’s Institutes of the Christian Religion, amongst others, this article evaluates Turretin’s view of the doctrine of sin and its relation to medieval and early-modern European theology. Ultimately, it argues that Turretin’s view of sin as a punishment of sin is born from his understanding of God’s holiness being demonstrated through his ‘vindicatory justice’ and Turretin’s self-understanding as an ‘orthodox’ theologian in the grand tradition of Western theology extending back to the Church Fathers.